Content and Language Integrated Learning: A study of the linguistic challenges facing English second language Grade 11 learners, and their teachers, in Biology - Webb, Victor N. (University of Pretoria, 2013)
Dissertation (M (Applied Language Studies))--University of Pretoria, 2006.